Evaluation of Discharge Calculation in Open Pit Mining - Kurniawan, Ivan; Damarnegara, Satria; Margini, Nastasia F (Institut Teknologi Sepuluh Nopember, 2023)
This study presents the discharge calculation of open pit mining drainage system. Open pit mining is one of surface mining methods when the location of the coal is near ground surface. This research uses open pit mine at PT Maruwai Coal as the case study. Several methods of discharge calculation are performed, such as: rational method, FJ Mock and HEC-HMS model. The drainage system of the mine is analyzed using spatial analysis. The runoff coefficient based on observation and theoretical value is compared. Each calculation is compared with observation data based on pump operation on the mine. Several challenge and limitation of each method is analyzed and several parameter recommendations are given. Runoff prediction for design rainfall also compared, based on each approach. This study result can be used to optimize the run-off management on open pit mining.